Hubungan Aktifitas Fisik, Kebiasaan Konsumsi Fast Food, Konsumsi Buah dan Sayur terhadap Obesitas pada Remaja - Ariyanto, Ariyanto; Fatmawati, Tina Yuli; Efni, Nel (Jurnal Akademika Baiturrahim Jambi, 2024)
Obesity problem in Indonesia still occurs in all age groups and socio-economic strata. According to Basic Health Research, the prevalence of overweight and obesity in the age group >18 years has increased by 21.8%. The high prevalence of obesity is supported by the prevalence of physical activity in the Population Aged >10 years of only 33.5%. Adolescents who are overweight are at risk of becoming obese as adults. The purpose of this study was to determine the relationship between physical activity, fast food consumption habits, fruit and vegetable consumption and obesity in adolescents. This research method uses an observational analytical design with a cross-sectional approach. This study was conducted at SMP N Kota Jambi. The sample in this study amounted to 57 people, the sampling technique was simple random sampling. The instruments used were questionnaires and anthropometric examination tools (scales and microtoice) with measurements of body weight and height to obtain BMI values. The data were then analyzed univariately and bivariately with the C-Square test. The results of the study showed that there was a relationship between physical activity habits, fruit and vegetable consumption with the incidence of obesity in adolescents and there was no relationship between fast food consumption and the incidence of obesity in adolescents. It is recommended that teenagers change their bad behavior related to food and nutrition into healthy, beneficial behavior and do more physical activity or exercise every day.